If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s + 4s = 2s Combine like terms: 2s + 4s = 6s 6s = 2s Solving 6s = 2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2s' to each side of the equation. 6s + -2s = 2s + -2s Combine like terms: 6s + -2s = 4s 4s = 2s + -2s Combine like terms: 2s + -2s = 0 4s = 0 Divide each side by '4'. s = 0 Simplifying s = 0
| X-1/10=x-9/2 | | w-8.1=6.4 | | 1982.596=2*3.14*8.2*8.2+2*3.14*8.2*h | | t*3-8=9 | | 2x^3-10x^2-71x-9=0 | | a*6+8=13 | | 4n+73=5 | | 4x+6=-54-8 | | 3y=15-x | | -77=-++55 | | =(3-2)X+2Y+2 | | y=3.40x+2.20 | | 2x-4=86 | | ln(2x)-ln(3)=5 | | 3x+17=11x+47 | | 6x+106=2x+108 | | -2n^2+9=-7n | | =X+2Y+2 | | n-13=86 | | a^2-6a=9 | | c-28=51 | | -2x^2=-2-3x | | 35/7=p | | 3b-4/2 | | -21=9a-15-3 | | 7=g/8 | | 6b-(5-4b)=25 | | 3(x-3)+6=4x+3 | | -21=9a-15 | | 4x+2(10-x)=28 | | (a^2b^-3)^3a^2b/a(2b)^-3 | | 12x+5=5x+20 |